PENGARUH BEBAN KERJA DAN BURNOUT TERHADAP KINERJA KARYAWAN PT PUTRATAMA BHAKTI SATRIA CISAUK BSD TANGERANG - Siti Salwa; Endah Asmarawati (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to analyze the effect of workload and burnout on employee performance at PT Putratama Bhakti Satria Cisauk BSD Tangerang. The research method uses a quantitative approach with simple and multiple linear regression techniques. The research sample consisted of 50 employees taken using the total sampling (saturated sampling) method, so the entire population was used as respondents. The hypothesis test results show that workload has a negative and significant effect on employee performance with a t-value (-4.178) > t-table (2.011) and a significance level of p = 0.000. The simple regression equation obtained is Y = 31.418 − 0.218X with an R Square value of 0.267, which means workload explains 26.7% of performance variation. Burnout also has a negative and significant effect on performance with a t-value (-4.499) > t-table (2.011) and a significance level of p = 0.000. The simple regression equation obtained is Y = 30.397 − 0.214X with an R Square value of 0.297, meaning burnout explains 29.7% of performance variation. Simultaneously, workload and burnout have a negative and significant effect on employee performance with an F-value (20.050) > F-table (3.195) and a significance level of p = 0.000. The multiple regression equation obtained is Y = 34.268 − 0.175X₁ − 0.177X₂ with an R Square value of 0.460, which means both variables can explain 46.0% of employee performance variation. These findings confirm that reducing workload and burnout has a real impact on improving employee performance. Therefore, proportional workload management and burnout prevention efforts are crucial factors in maintaining productivity and work effectiveness in the company. Keywords: Workload, Burnout, Employee Performance, PT Putratama Bhakti Satria Cisauk